Lumbar 4-5 Laminoplasty for Ligation of Dural Fistula: 2-Dimensional Operative Video. Issue 3 (13th December 2019) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: The goal of treatment for spinal dural arteriovenous fistulas is disconnection of the fistulous point to eliminate venous congestion-associated hypoperfusion and mass effect. The nidus can be surgically excised or disconnected from the arterial feeder just proximal to the dilated venous plexus. This patient had a filus terminale dural arteriovenous fistula. The patient had multiple findings of myelopathy, which prompted the imaging evaluation that revealed prominent flow voids and significant caudal thoracic spinal cord edema. Preoperative digital subtraction angiography demonstrated a fistulous point at the lumbar 4 level. A lumbar 4 and lumbar 5 laminoplasty was performed for spinal canal access. Following achievement of intradural access, exploration was performed, augmented by indocyanine green fluoroscopy. The filum terminale was then transected, and the fistula was then completely excised to achieve surgical cure. Following the procedure, the patient's myelopathy improved, and she regained ambulatory status. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona .